The Effectiveness of PBL Assisted by H5P Interactive Video in Improving Mathematics Literacy of Junior High School Students - Intan Nurmala; Sumliyah Sumliyah; Titi Rohaeti (Journal of General Education and Humanities, 2025)
The low mathematical literacy of junior high school students in Indonesia remains a challenge, as reflected in PISA results that consistently place Indonesia at the bottom in mathematical reasoning. This study aims to examine the effectiveness of Problem-Based Learning (PBL) assisted by H5P interactive videos in improving mathematical literacy compared to PBL without digital media. A quasi-experimental method with a Nonequivalent Control Group Design was applied to two grade VIII classes of a state junior high school in Cirebon, each consisting of 36 students. The instrument was a mathematical literacy test based on three PISA indicators: formulating, employing, and interpreting. Data analysis included normality, homogeneity, and an Independent Samples T-Test, supported by N-gain calculation. The results showed no significant difference in pre-test scores between the groups, indicating comparable initial ability. However, the experimental class achieved an N-gain of 0.71 (medium–high category), higher than the control class of 0.38 (low–medium category), with a significance level of 0.000 < 0.05. These findings confirm that integrating H5P into PBL significantly improves students' mathematical literacy. The study concludes that interactive media serve not only as a learning aid but also as a pedagogical tool that fosters participatory, contextual, and meaningful learning, providing practical recommendations for mathematics teachers to adopt innovative digital approaches.